Analysis of the Suitability of Science Content in YouTube Learning Videos for Elementary School Students - Firayani, Firayani (Scientica Education Journal, 2025)
This study aims to analyze the suitability of Natural Science (IPA) learning video content available on the YouTube platform with the elementary school (SD) curriculum in Indonesia. This study used a descriptive qualitative method with a content analysis approach to a number of science learning videos selected based on certain criteria, such as theme relevance, number of views, and age segmentation. The analysis instrument was compiled based on the core competency indicators in the 2013 Curriculum and the Independent Curriculum. The results showed that most videos were thematically aligned with the curriculum, but still found inaccurate scientific concepts, language use that was not appropriate to students' cognitive levels, and minimal relevance to everyday life contexts. Videos from official or verified channels generally showed better content quality. This study recommends the need for evaluative guidelines for teachers and parents in selecting digital learning media, as well as encouraging improvements in the quality of YouTube-based educational content to support meaningful science learning at the elementary school level